Glucosamine inhibits extracellular matrix accumulation in experimental diabetic nephropathy - Teuma, Loic; Eshwaran, Rachana; Tawokam Fongang, Ulrich; Wieland, Johanna; Shao, Feng; Lagana, Maria Luisa; Wang, Yixin; Agaci, Ane; Hammes, Hans-Peter; Feng, Yuxi (Frontiers in nutrition, 2022)
IntroductionGlucosamine, the intermediate metabolite of the hexosamine biosynthesis pathway (HBP), is widely used as a supplementary drug in patients with osteoarthritis. However, its consequences in such patients concomitantly suffering from diabetic nephropathy is unknown.MethodsThe aim of the study was to investigate the effect of exogenous administration of glucosamine in the diabetic kidney. A mouse model of streptozotocin-induced diabetic nephropathy in vivo and cultured endothelial cells in vitro were used in the study. The mice were treated with glucosamine for 6 months. Renal function was evaluated by metabolic cage, and histology of the kidney was estimated by periodic acid-schiff (PAS) staining. The expression of related genes was assessed by real-time PCR, immunofluorescence staining, immunoblotting and ELISA.ResultsThere was no significant difference in urinary albumin secretion, relative kidney weight, or creatinine clearance between the groups treated with glucosamine and controls. Assessment of the kidney demonstrated reduction in mesangial expansion and fibronectin expression in the diabetic glomeruli treated with glucosamine. Glucosamine treatment significantly decreased α-smooth muscle actin (α-SMA) protein expression in both diabetic and control kidneys, whereas the expression of other fibrosis-related genes and inflammatory factors was unaltered. Moreover, α-SMA colocalized with the endothelial marker CD31 in the diabetic and control kidneys, and glucosamine reduced α-SMA+ ECs in the diabetic glomeruli. In addition, glucosamine suppressed α-SMA expression in endothelial cells treated with or without high glucose.DiscussionIn summary, this is the first report to show that glucosamine reduces mesangial expansion and inhibits endothelial-mesenchymal transition in diabetic nephropathy. The underlying mechanisms need to be further investigated.